Can the Reaction Mechanism of Radical Solution Polymerization Explain the Microgel Final Particle Volume in Precipitation Polymerization of N‐Isopropylacrylamide?. Issue 13 (27th May 2015) - Virtanen, Otto L. J.; Ala‐Mutka, Helmi M.; Richtering, Walter
<x xml:space="preserve">Abstract</x> Precise particle size customization is a key requirement for the applications of stimuli‐sensitive poly(N‐isopropylacrylamide) microgels. No empirically supported mechanism has been presented to explain the microgel particle size dependence on polymerization conditions. In this work, nonstirred precipitation polymerization is employed to address this question. It is argued that the reaction proceeds by radical solution polymerization mechanism rather than as emulsion polymerization. The number of particles in the batch, and the microgel particle volume, is shown to correlate with the charge density of the particles determined by the kinetic chain length. Cross‐linking efficiency is recognized to be an important factor in the particle nucleation. Properties of radical solution polymerization, such as differences in the rate of decomposition of thermally decomposing initiator and redox initiator, are used to tune the particle number density in the batch. Contemporary synthesis approaches, including temperature‐programmed synthesis, are discussed in the context of these results.